2023
DOI: 10.1038/s41598-023-34576-z
|View full text |Cite
|
Sign up to set email alerts
|

The factors associated with mortality and progressive disease of nontuberculous mycobacterial lung disease: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis aimed to comprehensively evaluate the factors associated with mortality and progressive disease in NTM-LD patients. We conducted a literature search to identify the eligible studies, dated between January 1, 2007, and April 12, 2021. Forty-one studies with total 10,452 patients were included. The overall all-cause mortality rate was 20% (95% CI 17–24%). The overall rates of clinical and radiographic progressive disease were 46% (95% CI 39–53%) and 43% (95% CI 31–55%), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Despite recent progress made in developing risk scores to predict mortality associated with NTM-PD, little progress has been made to predict individual disease progression in patients without cavitary and/or severe disease. The BACES score is composed of low BMI (<18.5 kg/ m 2 ), advanced age (�65 years), presence of cavity, elevated ESR, and male sex which can predict mortality in patients with NTM pulmonary disease [16,21]. However, most of these were not significantly associated with progressive disease in our study, and may not directly affect the NTM-LD progression.…”
Section: Plos Onecontrasting
confidence: 59%
See 1 more Smart Citation
“…Despite recent progress made in developing risk scores to predict mortality associated with NTM-PD, little progress has been made to predict individual disease progression in patients without cavitary and/or severe disease. The BACES score is composed of low BMI (<18.5 kg/ m 2 ), advanced age (�65 years), presence of cavity, elevated ESR, and male sex which can predict mortality in patients with NTM pulmonary disease [16,21]. However, most of these were not significantly associated with progressive disease in our study, and may not directly affect the NTM-LD progression.…”
Section: Plos Onecontrasting
confidence: 59%
“…Recently, a study reported that high serum levels of Krebs von den Lungen-6 (KL-6) was associated with disease progression in MAC lung disease [24]. Further, systemic inflammatory markers, history of TB, cough, weight loss, presence of cavity and malnutrition were also reported as predictive for disease deterioration in NTM-LD [21,22,25,26]. However, the results are highly heterologous and depend on the study patients' characteristics, the study settings, and lack of controlled clinical trials renders them inconclusive.…”
Section: Plos Onementioning
confidence: 99%
“…Individuals aged 65 and older showed a higher proportion of men, and a higher proportion of patients with BMI <18.5 kg/m 2 ( Table 3 ), indicative of a poorer NTM-PD prognosis. Given the anticipated worse outcomes in the older demographic [ 36 ], proactive treatment consideration is critical. Notably, treatment-related adverse events are commonly reported among NTM-PD patients [ 37 ], and those over 65 in our study also exhibited a higher prevalence of underlying respiratory (COPD, asthma, and interstitial lung disease) and non-respiratory (hypertension, diabetes, chronic kidney diseases, and chronic heart disease) conditions, necessitating vigilant monitoring for drug-related adverse events during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients affected by NTM-PD, weight loss and low BMI have been associated with disease progression, unfavorable outcomes, and increased mortality rates, even among those receiving treatment [ 31 ]. Although studies exploring the benefits of nutritional supplementation in patients with NTM-PD remain scarce, it is widely acknowledged that nutrition support and weight gain play a crucial role to help patients fight infection.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%